Análise do modelo curricular da faculdade salesiana dom bosco de acordo com os parâmetros estabelecidos pela associação brasileira de ensino e pesquisa em serviço social - Alves de Azevedo, Soraya (2011)
The research aimed to investigate the current model curriculum of the course of Social Service at the Faculdade Salesiana Dom Bosco in accordance with the parameters of Brazilian Association of Teaching and Research, delimiting fortresses and weaknesses. It’s Justified because of the countless social changes equipped a new vision of man and society, embodied in the expansion and diversification of curricular models, in order to meet the demands imposed by contemporary on the labor market, educational policies and the politicalinstitutional teaching. The problem of the research sought to determine whether what was recommended by the Brazilian Association of Education and Research (ABEPSS) as the parameter national curriculum for the courses of Social Service has been reflected in the curriculum adopted by the Faculdade Salesiana Dom Bosco, unveiling its strengths and weaknesses. The methodology used was quantitative and qualitative.